Problem Based Learning to Improve First Grade Pancasila Learning Outcomes: Pembelajaran Berbasis Masalah untuk Meningkatkan Hasil Pembelajaran Pancasila pada Kelas 1 - Armalasari, Olivia Nur; Kurniawan, Machful Indra (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Education in Indonesia requires learning approaches that foster active student engagement, particularly in early grades. Specific Background: Pancasila Education in grade 1 often faces issues such as low motivation and passive learning due to traditional teacher-centered methods. Knowledge Gap: Limited studies have examined the use of Problem Based Learning (PBL) to strengthen conceptual understanding of Pancasila in early elementary school. Aims: This study aims to improve learning outcomes through the implementation of PBL in grade 1 Pancasila Education. Results: Classroom Action Research involving two cycles showed a significant increase in mastery, from 31.25% in the pre-cycle, to 56.25% in cycle I, and reaching 93.75% in cycle II. Novelty: This study provides early-grade empirical evidence of PBL’s effectiveness for Pancasila concepts using contextual problem exploration. Implications: The findings highlight that well-structured PBL can increase student participation, responsibility, and conceptual understanding in civic-related learning. Highlights:• PBL significantly increased grade 1 Pancasila learning outcomes• Students became more active and disciplined through structured class rules• Two-cycle PTK showed consistent improvement in mastery levels Keywords: Problem Based Learning, Pancasila Education, Learning Outcomes, Early Elementary, Classroom Action Research